Comparison of Single Incision and Conventional Laparoscopic Surgery for Surgical Sterilization - Karasu, Yetkin; Kavak Comert, Duygu (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: To compare the intraoperative characteristics and postoperative pain levels of single incision and conventional laparoscopic surgeries performed for surgical sterilization. Study Design: A single center prospective observational study was conducted to compare the conventional and single incision laparoscopic (SIL) partial salpingectomies performed for surgical tubal sterilization. In total of 110 women, 62 in the conventional laparoscopy and 48 in the SILS group participated in the study. The main outcome measures were peritoneal entry time, total operation time, amount of bleeding, intraoperative complications, post-operative pain scores, additional analgesic requirements, and length of hospital stay. Statistical analysis was accomplished using the chi-square test or Mann Whitney U test, where appropriate. Results: Demographical findings did not differ between the two groups (p>0.05). Similarly, total operation time, rates of intraoperative complications, conversion to laparotomy, length of hospital stay, pre and postoperative hematocrit levels were not significantly different between the groups. Peritoneal entry time was shorter in the SIL group (7.1 min. vs. 4.8 min., p<0.001). Additional analgesic requirements, postoperative pain scores in the recovery room and at 6th, 12th, and 24th hours were not different between the groups (p>0.05). Conclusion: SILS seems a safe and feasible alternative to conventional laparoscopy for surgical tubal sterilization. Keywords: Partial salpingectomy, Tubal ligation, Contraception, Surgical sterilization, Single Incision Laparoscopy